2019
DOI: 10.1007/s10616-019-00310-9
|View full text |Cite
|
Sign up to set email alerts
|

Boron mediated 2D and 3D cultures of adipose derived mesenchymal stem cells

Abstract: Boron (B), which is a beneficial bioactive element for human, has an increasing interest in tissue engineering for the last 5 years. However, the effective B concentration in cell culture is still unknown. The aim of the present study is to investigate in vitro osteogenic potential of mesenchymal stem cells, isolated from adipose tissue (AdMSCs), on boron containing 2D and 3D cell cultures. At first, the effects of B concentrations between 1 and 20 lg/mL were evaluated on the survival and osteogenic differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The high demand for biomaterial scaffolds for providing the naturally derived platform mimicking the structure and composition of natural bone tissue, delivering the cells to the local site of injury and facilitating the repair of bone defects has opened a window of hope in the treatment of large bone tissue fractures. [34][35][36] ECM of the placenta contains various bioactive molecules, including cytokines and growth factors such as EGF, bFGF, PDGF, IGF-1, and VEGF, suitable for bone, cartilage and blood vessel regeneration. 37,38 Placental tissues are readily available and with fewer ethical restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…The high demand for biomaterial scaffolds for providing the naturally derived platform mimicking the structure and composition of natural bone tissue, delivering the cells to the local site of injury and facilitating the repair of bone defects has opened a window of hope in the treatment of large bone tissue fractures. [34][35][36] ECM of the placenta contains various bioactive molecules, including cytokines and growth factors such as EGF, bFGF, PDGF, IGF-1, and VEGF, suitable for bone, cartilage and blood vessel regeneration. 37,38 Placental tissues are readily available and with fewer ethical restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the mechanical and bioactive properties of chitosan scaffolds, Akdere et al coated the scaffolds with HAp (hydroxyapatite) or B-HAp (boron doped hydroxyapatite). The results showed that a high number of AdMSCs attached and proliferated on HAp and B-HAp coated scaffolds when compared to bare chitosan scaffolds ( Akdere et al, 2019 ). In another study, it was reported that MSCs formed spheroids that kept attached for 10 days on the chitosan (77.7% DD) and chitosan-hyaluronan membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture studies were carried out with rat adipose tissue derived mesenchymal stem cells (rAdMSCs) at passages between 4 and 6. These primary cells were isolated and characterized by three different lineage differentiation and CD marker analysis in our previous study under the approval of the Non-invasive Clinical Research Ethic Committee of Hacettepe University (number: 2015/32-04, Ankara, Turkey) ( Akdere et al, 2019 ). The cells were cultured in 1% (v/v) L-glutamine (Sigma, Germany), 15% (v/v) FBS (fetal bovine serum, Biowest, France) and antibiotics (10 units/mL penicillin, 10 μg/mL streptomycin, 50 μg/mL gentamycin, 250 ng/mL Amphotericin B; Sigma, Germany) containing alpha-Minimum Essential Medium (α-MEM, Sigma, Germany), cell maintenance medium (CMM).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations